Nucleophilic C4-selective (hetero) arylation of pyridines for facile synthesis of heterobiaryls - Kim, Kewon; You, Euna; Hong, Sungwoo (Frontiers in Chemistry, 2023)
The synthesis of heterobiaryl compounds holds significant value in organic chemistry due to their extensive range of applications. Herein, we report a highly efficient strategy for conducting C4-selective (hetero)arylation of pyridines using N-aminopyridinium salts. The reaction proceeds readily at room temperature in the presence of a base, thus eliminating the requirement for catalysts or oxidants. This method allows for the installation of various electron-rich (hetero)aryl groups on pyridines, resulting in the streamlined synthesis of highly valuable C4-(hetero)aryl pyridine derivatives, which are otherwise challenging to acquire via conventional methods. This simple and straightforward method will facilitate access to a range of heterobiaryl compounds thereby promoting their application in various scientific disciplines.